The Increasing Trend in Global Ranking of Websites of Iranian Medical Universities during January 2012-2015 - Nahid RAMEZAN GHORBANI; Yousef FAKOUR; Seyed Ali NOJOUMI (Tehran University of Medical Sciences, 2017)
Background: Researchers and academic institutions need assessment and rating to measure their performance. The criteria are designed to evaluate quality and adequacy of research and welcome by most universities as an international process to increase monitoring academic achievements. The study aimed to evaluate the increasing trend in global ranking of Iranian medical universities websites emphasizing on comparative approach. Methods: This is a cross-sectional study involving websites of Iranian medical universities. Sampling was conducted by census selecting universities affiliated to the Ministry of Health in webometrics rating system. Web sites of Iranian medical universities were investigated based on the webometrics indicators, global ranking as well as the process of changing their rating. Universities of medical sciences were associated with improved ratings in seven periods from Jan 2012 until Jan 2015. Results: The highest rank was in Jan 2014. Tehran University of Medical Sciences ranked the first in all periods. The highest ratings were about impact factor in universities of medical sciences reflecting the low level of this index in university websites. The least ranking was observed in type 1 universities. Conclusion: Despite the criticisms and weaknesses of these webometrics criteria, they are critical to this equation and should be checked for authenticity and suitability of goals. Therefore, localizing these criteria by the advantages model, ranking systems features, continuous development and medical universities evaluation based on these indicators provide new opportunities for the development of the country especially through online media.